2005
DOI: 10.1177/0363546504274148
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Lacrosse Injuries in High School-Aged Girls and Boys

Abstract: The overall injury rates for boys' and girls' high school lacrosse were significantly lower than those for collegiate play. Significant differences existed between adolescent boys and girls with respect to injury mechanisms, body parts injured, and player and team activity at the time of injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
126
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(140 citation statements)
references
References 19 publications
13
126
1
Order By: Relevance
“…The concussion IR of 1.58/1000 exposures in our sample of youth ice hockey players aged 12 to 18 years was comparable to rates reported for other youth sports. 8,10,[13][14][15] In fact, in a recent study of youth football players, researchers reported a total concussion IR of 1.76/1000 exposures, 10 which is similar to the rate reported in the current study. In the current study, players had nearly 3 times more concussions per exposure in games compared with practices.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The concussion IR of 1.58/1000 exposures in our sample of youth ice hockey players aged 12 to 18 years was comparable to rates reported for other youth sports. 8,10,[13][14][15] In fact, in a recent study of youth football players, researchers reported a total concussion IR of 1.76/1000 exposures, 10 which is similar to the rate reported in the current study. In the current study, players had nearly 3 times more concussions per exposure in games compared with practices.…”
Section: Discussionsupporting
confidence: 84%
“…10 It is likely that similar findings would be supported among youth ice hockey players. The primary purpose of this study was to prospectively examine concussion IRs in a multisite cohort of male and female youth ice hockey players aged 12 to 18 years across a competitive season, and to compare IRs in games and practices, and between younger (12)(13)(14) and older (15)(16)(17)(18) players.…”
mentioning
confidence: 99%
“…[46][47][48] Injury incidences in high school basketball (1.94/1000 AEs), 46 soccer (2.4/1000 AEs), 48 and football (gridiron, 3.5/1000 AEs) 47 were all lower than those reported by Collins et al 19 (5.2/1000 AEs). Despite using a slightly different definition of time loss as more than 48 hours, studies of high school lacrosse (2.89/1000 playing hours) 49 and youth soccer (11.2/1000 match hours) 50 players also showed lower injury rates than did rugby players.…”
Section: Comparison With Other Adolescent Sportsmentioning
confidence: 99%
“…Rugby, ice hockey, and lacrosse also account for higher rates of concussions but are often club sports, which limits their data inclusion in the larger high school sports epidemiologic studies. [34][35][36][37] …”
Section: Epidemiology Of Concussionmentioning
confidence: 99%